DETERMINAN KEPUTUSAN HEDGING PADA PERUSAHAAN MANUFAKTUR - Lina Wati, - (2019)
This research aims to know the influence of liquidity, leverage, growth opportunities and firm size of hedging decision on manufacturing companies in Indonesia Stock Exchange period 2016 to 2017.The sampling method is using purposive sampling method and obtained 44 samples of companies that meet the criteria and 88 firm-year observation. Analytical techniques applied in this study is the analysis of logistic regression. The results of the test were obtained (1) liquidity has noteffect on the hedging decision. (2) Growth opportunity has not effect on the hedging decision. (3) Firm size and leverage shows a significant effect on the hedging decision.